RETRACTED: Indentation parameters for Brinell hardness measurement of low carbon steels - Udalov A.V.; Udalov A.A.; Norin E.G. (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001